The Existence of Pamali in Character Building of Javanese Women in Kranggan Village, Pakisaji, Malang Regency - Sheehan, Aurezza Bryna; Kriyantono, Rachmat (Tuturlogi: Journal of Southeast Asian Communication, 2025)
As local wisdom inherent in Javanese life, pamali is often considered a myth or taboo. Many Indonesians use pamali as a guideline to behave according to morals and ethics. People who believe in the existence of pamali, believe that violating pamali can bring certain risks or consequences. The messages and meanings contained in pamali are the result of social construction that is closely related to reality. Reality can occur due to the process of action and interaction between human individuals. One form of social construction of pamali is the existence of pamali expressions that tend to be aimed at women who are considered to discredit the existence of women. This study aims to describe the messages and meanings of pamali that are communicated and constructed, so that they can play a role in shaping the character of Javanese women. This research uses a constructivistic paradigm and qualitative research methods with data collection techniques of observation and in-depth interviews conducted in Kranggan Village, Pakisaji, Malang Regency. This research produces five new propositions based on the results of informants' answers who have communicated and constructed the message or meaning contained in pamali, so that it plays a role in the character building of Javanese women.